Vaccination Policy and Trust - Artyom Jelnov; Pavel Jelnov (Global Labor Organization (GLO), 2021)
We study the relationship between trust and vaccination. We show theoretically that vaccination rates are higher in countries with more transparent and accountable governments. The mechanism that generates this result is the lower probability of a transparent and accountable government to promote an unsafe vaccine. Empirical evidence supports this result. We find that countries perceived as less corrupt and more liberal experience higher vaccination rates. Furthermore, they are less likely to adopt a mandatory vaccination policy. One unit of the Corruption Perception Index (scaled from 0 to 10) is associated with a vaccination rate that is higher by one percentage point (pp) but with a likelihood of compulsory vaccination that is lower by 10 pp. In addition, Google Trends data show that public interest in corruption is correlated with interest in vaccination. The insight from our analysis is that corruption affects not only the supply but also the demand for public services.
Keywords: I18; 330; vaccination; corruption